Power aware framework for scheduling tasks in grid-based workflows. (1st January 2015) - Reddy, T. Sunil Kumar; Krishna, P. Venkata; Reddy, P. Chenna
Grid computing is a conglomeration of computer resources which explores, exploits and shares various virtual resources in order to enhance the capabilities of parallel CPU. The issue of the consumption of energy over the grid is pivotal during the workflow scheduling, which is generally estimated considering the criteria of usage of power per device, process or service. This paper postulates a framework called power estimator and reducer for multi-core architecture in grid (PERMA-G), which is a modified and revised version over its predecessor framework of PERMA developed by Rajasekhara Babu et al. (2013), capable of addressing the issues of estimating and reducing power in multi-core processors. PERMA-G proves versatile in estimating the consumption of power and the computation capabilities of various resources for multi-core processor environments based on grid. Through dynamic processes it extracts several complexities involved in the tasks and schedules of computation by a method of workflow leading to reduced power consumption, cost efficacy and contracted execution time in general.